2018
DOI: 10.4025/jphyseduc.v29i1.2915
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Models of Fatigue and Physical Performance

Abstract: The origin of fatigue has been the focus of studies involved in sports performance, due to the necessity to clarify the mechanistic bases for the reduced capacity to perform considerable effort intensities. According to the traditional conception of fatigue, mechanisms may encompass peripheral and central sites of fatigue. Peripheral fatigue is understood as events related to an inefficient tissue oxygen delivery, metabolic accumulation, muscular acidosis and muscle substrate depletion. In contrast, the centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…Such an ineffectiveness of caffeine in improving peripheral responses may be related to the muscle contraction stimulation frequency of the submaximal IC exercise, as it has been proposed that caffeine changes muscle properties through alterations in calcium release rather than through potassium accumulation [33]. Thus, assuming that calcium metabolism is associated with force losses mainly in frequencies <20–30 Hz [7,34,35] and that our submaximal IC exercise required a muscle contraction frequency mostly higher than 50 Hz [36], perhaps caffeine ingestion is ineffective in improving key muscular properties enhance muscle endurance performance during submaximal IC. Somehow, the fact that coherence analysis indicated a significant coupling between gamma wave EEG (30–50 Hz) and EMG may reinforce this argument.…”
Section: Discussionmentioning
confidence: 99%
“…Such an ineffectiveness of caffeine in improving peripheral responses may be related to the muscle contraction stimulation frequency of the submaximal IC exercise, as it has been proposed that caffeine changes muscle properties through alterations in calcium release rather than through potassium accumulation [33]. Thus, assuming that calcium metabolism is associated with force losses mainly in frequencies <20–30 Hz [7,34,35] and that our submaximal IC exercise required a muscle contraction frequency mostly higher than 50 Hz [36], perhaps caffeine ingestion is ineffective in improving key muscular properties enhance muscle endurance performance during submaximal IC. Somehow, the fact that coherence analysis indicated a significant coupling between gamma wave EEG (30–50 Hz) and EMG may reinforce this argument.…”
Section: Discussionmentioning
confidence: 99%
“…Each question is rated on a 5-point Likert scale (0 = no problem; 4 = very severe problem), resulting in a total score that ranges from 0 to 28. The following categories of insomnia were used to interpret the overall score: severe insomnia (22)(23)(24)(25)(26)(27)(28), moderate insomnia (15)(16)(17)(18)(19)(20)(21), sub-threshold insomnia (8)(9)(10)(11)(12)(13)(14), and no insomnia (0-7) [28]. The validity of the ISI has been established in various populations using robust methodologies, including Southeast Asians [30][31][32].…”
Section: Insomnia Severity Index (Isi)mentioning
confidence: 99%
“…The various reasons suggested for post-stroke fatigue include increased tissue inflammation [ 9 ], alterations in excitability, and disruptions in the connections between various brain areas due to stroke pathology [ 10 ]. Central models of fatigue attribute this condition to changes in the functioning of the CNS [ 11 ]. The reported prevalence of PSF is around 50%, and it may improve or worsen over time [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A greater peripheral fatigue was detected as the shorter cycling time trial progressed (i.e., 4 km cycling time trial), in contrast to the greater central fatigue found after longer cycling time trials such as 20 km and 40 km. 20 The hypothesis was that participants completing the 4 km cycling trial faced higher levels of muscle metabolites-induced neuromuscular fatigue (47) such as hydrogen and potassium accumulation, 54 , 55 thus contrasting to centrally mediated reductions in motor command and voluntary activation in 40 km cycling time trial. 56 Somehow, this different exercise intensity-neuromuscular fatigue interplay may provide rationale to the controversial results involving endurance exercise protocols, as addressed below.…”
Section: Type Of Exercise Protocolmentioning
confidence: 99%